Identifikasi mikroplastik pada siput Genus Bellamya sp. dari segmen Wonokromo, Tegalsari dan Gubeng Kali Mas Surabaya - Aliyansyah, Gunawan (Program Studi Biologi Fakultas Sains dan Teknologi Universitas Islam Negeri Alauddin Makassar, 2024)
Plastic waste remains a problem in Indonesian waters. The increase in plastic waste is related to the increasing population. Mismanaged and discarded plastic in the water will degrade into plastic larger than 5 mm, called microplastics. Kali Mas river in Surabaya has the potential to be contaminated due to its flow characteristics through urban areas, trade, and densely populated settlements. Microplastics have the potential to contaminate organisms, one of which is the snail of the genus Bellamya sp., which is abundant in the Kali Mas river. To assess the potential contamination of microplastics in snails, it is necessary to identify microplastics in snails of the genus Bellamya sp. to determine the type and abundance of microplastics in snail samples of the genus Bellamya sp. The research method is divided into several stages, namely sampling, sample preparation, sample identification, and data analysis. The study was conducted in three segments of the Kali Mas river in Surabaya: Wonokromo, Tegalsari, and Gubeng. The research results show that four types of microplastics were found in snails of the genus Bellamya sp. in the form of fiber, filament, fragment, and film. The highest average abundance of total microplastics was in the Tegalsari segment, with 2.53 particles/ind, followed by the Wonokromo segment, with 2.13 particles/ind, and the Gubeng segment, with 1.6 particles/ind. Microplastics can have adverse effects on organisms such as snails of the genus Bellamya sp., such as reduced appetite and can serve as transport agents to other organisms, including humans.